Series of cases of acute acquired comitant esotropia in children associated with excessive online classes on smartphone during COVID-19 pandemic; digital eye strain among kids (DESK) study-3. (3rd July 2021) - Mohan, Amit; Sen, Pradhnya; Mujumdar, Deepti; Shah, Chintan; Jain, Elesh
ABSTRACT: Extra time of sitting in front of a digital device is required for e-learning by children during Corona virus (COVID-19) pandemic which can lead to many ocular problems including digital eye strain (DES). In view of increased incidence of DES in children, multiple studies had been conducted in central India to assess the eye strain in children due to excessive online classes as a research project named "Digital eye strain among kids (DESK) study." This study DESK-3 aimed to report series of cases of acute acquired comitant esotropia (AACE) in children attending online classes during COVID-19 pandemic. Children aged 6–18 years with recent onset of esotropia of < 1-month duration without any similar history in past presented in month of July-August 2020 at a tertiary children eye care hospital were evaluated. Data collection included age and gender of child, presence or absence of diplopia, visual acuity, duration of smartphone use, duration of online classes, angle of deviation for near and distance and cycloplegic refraction. Total eight children of AACE were included in the study. The mean age of children was 12.5 ± 4.2 years. All eight were males. The mean duration of smartphone use was 4.6 + 0.7 hours per day. All children were attending online classes > 4 hours per day on smartphone of average size 5.5 inches. Five children were emmetropic, one myopic, one pseudomyopic and one hyperopic. The angle of deviation for near and distance were 48.1 ± 16.4 PD and 49.3 ± 15.9 PD respectively with normal ocular motility. Seven children complained of horizontal diplopia in all gazes. Neurological examination and CT scan of brain and orbit was normal in all patients.  Two months before the lockdown only one case was identified as compared to eight during the lockdown. Prolonged near work during smart phone use for e-learning might lead to the development of AACE in children.